The Impact of Exogenous Shocks on Households in the Pacific : A Micro-Simulation Analysis - Cororaton, Caesar B.; Knight, David S. (World Bank Group, Washington, DC, 2014)
This paper seeks to provide evidence on the extent of household vulnerability to exogenous economic shocks in the Pacific region and consider policy options that help to manage this risk. Characteristics of the region such as remoteness, small size, dispersion, and urbanizing populations lead to pronounced vulnerabilities. The paper presents macroeconomic and distributional analysis and complements it with results of a micro-simulation model customized for this work based on a model used previously by the World Bank to analyze the impacts of the Food and Fuel Price Crisis. The results of micro-simulations serve to highlight the very high levels of economic vulnerability faced in the region. Impacts of economic shocks are not confined to well-off individuals, but have major impacts on the poor. Even moderate shocks are likely to push sizeable fractions of the population below the poverty line. The shocks considered are not worst case scenarios, but those that can and have occurred frequently. The results show that households are hard hit by increases in oil prices, especially in remote islands where freight costs are higher, while countries on aggregate, and individual households, are exposed to volatility in the prices of the one or two imported food commodities that they depend on. Livelihoods are also often driven by external demand. In particular, many poor households in countries like Papua New Guinea have livelihood strategies centered on cash crops. The results point to the importance of helping households of the Pacific to manage the risk inherent in their lives while prudently using macroeconomic tools at the disposal of the government.